Production - Domestic - Oil and Gas in Missouri in 1936 - Frank C. Greene (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1937)
Drilling for oil and gas in Missouri continued at a slightly lower rate than has been prevailing. A summary of operations for the past few years as compiled and published by the Missouri Geological Survey and Water Resources is as follows: Two oil pools are being developed in Cass County. Neither area has been drilled completely, and detailed descriptions will not be given at this time. In the Endicott pool in the southern part of T. 44 N., R. 33 W., oil is found in the Warrensburg sand, which is now considered to be the Big Lake sand of eastern Kansas. The top of the sand is about 125 ft. below the Herthalimestone. The best well is reported to have made 14 bbl. per day for the first four days. The oil is 30" to 32' BB. gravity. This is the only pool in the state, aside from the older areas on the east and west edges of Lees Summit, Jackson County, that is producing oil from the Warrensburg sand. Drilling continues in the Knoche pool in the central part of T. 46 N., R. 33 W., where the oil is found in the Squirrel sand. The oil produced by both these pools is sold by truck in Kansas City.